2021
DOI: 10.2217/bmm-2020-0425
|View full text |Cite
|
Sign up to set email alerts
|

Lower Levels of Triiodothyronine Are Associated with Poor Hemodynamic Profile and All-Cause Mortality in Heart Failure

Abstract: Background: We aimed to assess the association of triiodothyronine (T3) hormone with invasive hemodynamic parameters and all-cause mortality in heart failure with reduced ejection fraction (HFrEF). Results: About 483 HFrEF patients were enrolled. Patients with the lowest T3 tertile had advanced New York Heart Association (NYHA) classes, had higher uric acid, brain natriuretic peptide. T3 level had a positive correlation with cardiac index (CI) and a negative correlation with pulmonary vascular resistance and p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 24 publications
0
2
0
Order By: Relevance
“…It was previously shown that hypercorrection of a hypothyroid-like state, which occurs in heart failure, e.g., by decreased TH receptor expression or increased deiodinase type 3 activity in heart, may restore cardiac function (20,(48)(49)(50)(51). Similarly, systemic hypothyroidism may confer cardiovascular morbidity and mortality and hence is widely regarded as a TH substitution indication (52)(53)(54). However, recent studies challenge this "one-for-all" concept (55)(56)(57) and have advocated a more risk-based TH treatment strategy in case of hypothyroidism (58,59).…”
Section: Discussionmentioning
confidence: 99%
“…It was previously shown that hypercorrection of a hypothyroid-like state, which occurs in heart failure, e.g., by decreased TH receptor expression or increased deiodinase type 3 activity in heart, may restore cardiac function (20,(48)(49)(50)(51). Similarly, systemic hypothyroidism may confer cardiovascular morbidity and mortality and hence is widely regarded as a TH substitution indication (52)(53)(54). However, recent studies challenge this "one-for-all" concept (55)(56)(57) and have advocated a more risk-based TH treatment strategy in case of hypothyroidism (58,59).…”
Section: Discussionmentioning
confidence: 99%
“…Numerous studies have shown that hypothyroidism is an independent factor in uencing all-cause mortality in heart failure, both acute and chronic 8,9 . Currently, many studies have explored the prognostic factors of heart failure, with thyroid dysfunction being one of them 10,11 . However, there is a lack of speci c studies exploring the prognostic factors for hypothyroidism patients with heart failure and whether there are any differences compared to those without hypothyroidism.…”
Section: Introductionmentioning
confidence: 99%